THE THEME OF EXISTENTALISM IN GIRISH KARNAD'S 'TUGHLAQ' - Dr. Parul Singh (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2010)
This paper aims to present the existentialist features in Girish Karnad's play 'TUGLAQ'. Existentialism is a form of philosophical inquiry that explores the problems of human existence and is based on the subjective experience of thinking, feeling and taking action. It highlights the fact that every individual is unique in this world possessing freedom of choice and to execute their will. Individuals have to bear the responsibility for their actions as a result of their choices and thus shape their own destinies. Kierkegaard, the Danish philosopher